Effects of fibre reinforcements on properties of extruded alkali activated earthen building materials - Ojo, Emeso B.; Bello, Kabirat O.; Mustapha, Kabiru; Teixeira, Ronaldo S.; Santos, Sérgio F. [UNESP]; Savastano, Holmer (Elsevier, 2019)
The reaction between clay minerals present in soil and an alkaline solution has the potential to develop in situ binders, which can be harnessed in the development of earth based construction materials. To ascertain the efficacy of this stabilisation mechanism in conjunction with fibres which are commonly used in earthen construction, this study presents a comparative analysis of the reinforcing effect of different fibre types (sisal, Eucalyptus pulp microfibers and polypropylene) in an alkali activated stabilised soil produced using extrusion technique. An evaluation of flexural properties in oven-dry and saturated conditions was conducted to simulate mechanical response in ideal and extreme conditions to evaluate effect of fibre type and content (0–2 vol%). Physical properties were also studied and optimum fibre contents evaluated. Results show that with respect to lignocellulosic fibres, sisal fibre reinforcements yielded the most remarkable result with the highest statistically significant improvement in flexural strength (79% relative to the unreinforced matrix) compared to composites reinforced with Eucalyptus pulp micro-fibres. Improved packing density and attendant reduction in water absorption associated with sisal fibre reinforced composites was attributed to synergistic interactions between sisal fibres and alkali activated matrix. On the other hand, synthetic fibre reinforcement (polypropylene), which had no statistically significant effect on composite flexural strength, transformed brittle unreinforced matrices to deflection hardening composites due to weak fibre-matrix interactions. Sisal fibres have thereby demonstrated a significant reinforcing potential in extruded alkali activated earth-based materials and presents a satisfactory balance of strength, density and ductility for the development of eco-friendly building materials for low cost housing solutions.
Keywords: Earthen building materials; Fibre reinforced soils; Lignocellulosic fibres; Modulus of rupture